2006
DOI: 10.1007/s00531-006-0076-8
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic stoping as an important emplacement mechanism of Variscan plutons: evidence from roof pendants in the Central Bohemian Plutonic Complex (Bohemian Massif)

Abstract: The presence of numerous roof pendants, stoped blocks and discordant intrusive contacts suggests that magmatic stoping was a widespread, large-scale process during the final construction of the Central Bohemian Plutonic Complex, Bohemian Massif. The measured total length of the discordant contacts that cut off the regional cleavage and were presumably formed by stoping corresponds to about half of all contacts with the upper-crustal host rocks. In addition, at least some of the straight, cleavage-parallel intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…However, the common signatures of stoping are sharp discordant contacts between plutons and wall rocks and a lack of ductile deformation of the wall rocks (e.g. Glazner & Bartley, 2006; Žák, Holub & Kachlík, 2006). The northeast wall rocks of SEPC are deflected by the intrusion which means they were still ductile during the G0 emplacement, ruling out stoping as emplacement mechanism.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…However, the common signatures of stoping are sharp discordant contacts between plutons and wall rocks and a lack of ductile deformation of the wall rocks (e.g. Glazner & Bartley, 2006; Žák, Holub & Kachlík, 2006). The northeast wall rocks of SEPC are deflected by the intrusion which means they were still ductile during the G0 emplacement, ruling out stoping as emplacement mechanism.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Magmatic stoping, i.e., the formation and transport of host-rock pieces into a magma chamber, was recognized long ago (Goodchild, 1892;Daly, 1903), and stoped blocks have been described from many plutons worldwide (Daly, 1933;Buddington, 1959;Cobbing and Pitcher, 1972;Pitcher and Berger, 1972;Myers, 1975; Barnes et al, 1986Barnes et al, , 2003Becker and Brown, 1985;Miller and Paterson, 2001;Pignotta et al, 2001aPignotta et al, , 2001bYoshinobu et al, 2003aYoshinobu et al, , 2009Hawkins and Wiebe, 2004;Žák et al, 2006;Farris and Paterson, 2007;Lipman, 2007;Pignotta and Paterson, 2007). The extent and importance of stoping in magma chambers have been matters of vigorous scientifi c debate, as exemplifi ed by recent suggestions by Glazner et al (2004), Coleman et al (2004), and Glazner and Bartley (2006), who suggested that magmatic stoping is rare.…”
Section: Introductionmentioning
confidence: 96%
“…The extent and importance of stoping in magma chambers have been matters of vigorous scientifi c debate, as exemplifi ed by recent suggestions by Glazner et al (2004), Coleman et al (2004), and Glazner and Bartley (2006), who suggested that magmatic stoping is rare. Evaluating magmatic stoping is important given that stoping may (1) operate as an important material transfer process (Paterson and Fowler, 1993) during fi nal emplacement of plutons (Fowler, 1996;Žák et al, 2006;; (2) remove large sections of aureoles in host rock that preserved evidence for earlier material transfer processes and thus signifi cantly reduce the information available about the growth of chambers (Fowler, 1996;Wetmore et al, 2001;Yoshinobu et al, 2003a); (3) contribute to vertical exchange of mass and heat within the crust (Marsh, 1982;Furlong et al, 1991;Paterson et al, 1996;Farris and Paterson, 2007); and (4) contribute to the chemical contamination and cooling of magmas during their ascent and emplacement (Marsh, 1982;Furlong and Myers, 1985;McLeod et al, 1998;Barnes et al, 2004;Beard et al, 2005;Clarke, 2007;Erdmann et al, 2009).Whether common or rare, magmatic stoping is also of interest because it allows us to examine other long-standing issues. (1) How do fractures form in rocks at high temperatures (Rubin, 1993;Pignotta et al, 1999;Farris and Paterson, 2007;Pignotta and Paterson, 2007)?…”
Section: Introductionmentioning
confidence: 99%
“…Outcrop features that frequently occur in exposed plutons worldwide, and that are commonly cited as evidence for stoping, include (a) country-rock xenoliths and partly-detached roof pendants, (b) mixed xenolith populations, (c) local absence of contact-aureole rocks along pluton walls, (d) stepped intrusive contacts, and (e) host-rock structures that are discordant to intrusive contacts (e.g. refs 5 and 11, 12, 13, 14). However, the widespread observation of the above features is in contrast to the general lack of significant volumes of xenoliths in many plutons, which rarely exceeds 1% of outcropping pluton volumes (e.g.…”
mentioning
confidence: 99%